Design and simulation of a TTRH-EV supervisory controller for a proton SAGA 1.3 - Anbaran, Sajjad Abdollahzadeh; Idris, Nik Rumzi Nik; Aziz, Mohd Junaidi Abdul; Sutikno, Tole (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
This paper presents modeling and control design steps towards the vehicle hybridization process. The objectives are: a) to model a retrofitted proton SAGA, which is a through-the-road HEV; and b) to design and implement a supervisory control unit for this vehicle. The electric powertrain components required for conversion are sized using the ADVISOR software package. Physical models of both powertrains were modeled using the MATLAB Simscape toolbox and validated for their fidelity. A supervisory controller design and implementation for retrofitted TTRH-EV SAGA is based on the BSFC map and OOL of the engine. The control objective is to restrict engine operation within its optimum window. The controller was implemented using the MATLAB Stateflow toolbox. The complete model of the retrofitted TTRH-EV SAGA, together with the supervisory controller, was tested using standard drive cycles, and the results are presented.